2012
DOI: 10.1021/cg3001015
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Perfect Polycrystalline, Large-Grained Silicon Arrays Formed at Low-Temperature Ambient by Local Pyrolysis

Abstract: We report low-temperature ambient synthesis of high-quality, several micrometer thick polycrystalline silicon arrays on soda lime glass substrates by local pyrolysis, where SiH 4 gas is locally decomposed near and condensed on the resistively heated microheater arrays with an average growth rate of 50 nm/s. The silicon arrays had nearly perfect crystallinity and a minimum grain size larger than 0.2 μm, as determined by spatially resolved Raman spectroscopy and transmission electron microscopy. Boron-doped sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The release method was based on the formation of nanovoids at the LT‐GaN/Ti hetero‐interface and post‐mechanical treatment that accurately weakened the hetero‐interface. This method provides a new tool to realize flexible/stretchable blue or green EL devices having high performance, low cost, and scalability . The suggested transfer method might also be used for transferring global epitaxy‐based LED or vertical‐cavity surface‐emitting laser structures onto arbitrary substrates.…”
Section: Resultsmentioning
confidence: 99%
“…The release method was based on the formation of nanovoids at the LT‐GaN/Ti hetero‐interface and post‐mechanical treatment that accurately weakened the hetero‐interface. This method provides a new tool to realize flexible/stretchable blue or green EL devices having high performance, low cost, and scalability . The suggested transfer method might also be used for transferring global epitaxy‐based LED or vertical‐cavity surface‐emitting laser structures onto arbitrary substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [ 87 ] Copyright 2012, American Chemical Society. g) Synthesized GaN on Mo microheater bridge; (left) amorphous GaN, (center, right) polycrystalline GaN.…”
Section: Selective Synthesismentioning
confidence: 99%
“…[79][80][81][82][83][84][85][86] We have also demonstrated that an array of metallic microbridges such as molybdenum on ordinary glass substrates can be selectively heated up to 1200 °C while maintaining the substrate temperature below 100 °C (Figure 7 b), and have used the bridges for the synthesis of various materials, including polycrystalline silicon (p-Si) [ 87 ] and SWCNTs, [ 88 ] as well as for the annealing of lanthanum hexaboride (LaB 6 ) [ 89 ] and EL patterning. [ 90 ] We also successfully synthesized ZnO nanorods and ZnO/GaN coreshell nanorod heterostructures (Figure 7 c).…”
Section: Progress Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…6 (b)). Based on selective heating method [6][7][8][9][10], we achieved proof-of-concept level polycrystalline GaN (poly-GaN) using sodalime glass substrates at low-temperature ambient (Figs. 7 (a)-(e)).…”
Section: New Attempt To Form High-quality Gan At Low Temperaturesmentioning
confidence: 99%